Program Management of the Language Department in Teaching Arabic Language - Alfian, Riki; A'rafadi, Najah; Ma'sum, Afif (JURNAL IJ-ATL, 2024)
In Islamic educational institutions, Arabic language programs often encounter challenges in harmonizing traditional pedagogical values with contemporary instructional reforms. This research aims to analyze the strategic management of Arabic language instruction at an Islamic secondary school through a case study of the Language Department's leadership practices. Employing a qualitative approach, the study gathered data through interviews, documentation analysis, and participatory observation. Thematic analysis based on the Miles and Huberman model was used to uncover key patterns related to planning, leadership behavior, and stakeholder engagement. The findings reveal that the department effectively integrates managerial functions planning, organizing, leading, and controlling into its instructional management. The head of the department plays a dual role as both academic leader and cultural mediator, bridging traditional Arabic teaching methods with modern communicative approaches. Additionally, the department institutionalizes student feedback through structured forums and evaluation instruments, fostering participatory reform. These results highlight that sustainable improvement in Arabic language teaching is shaped not only by systematic planning but also by relational leadership and inclusive evaluation practices. The study contributes to a contextual framework for managing language programs in faith-based educational settings.